2017
DOI: 10.1109/tits.2017.2655498
|View full text |Cite
|
Sign up to set email alerts
|

Parked Cars are Excellent Roadside Units

Abstract: A comprehensive implementation of the envisioned traffic safety and efficiency applications of the IEEE 802.11p and WAVE standards assume the premise of the use of DSRC technology both as on-board units (OBUs) and as Roadside Units (RSUs). The high cost associated with RSUs, however, has so far prevented massive deployment of RSUs. Finding alternative solutions to this longstanding problem is therefore very important. In this paper, we propose a self-organizing network approach to using parked cars in urban ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Eckhoff et al [5] introduced a novel scheme to emit cooperative awareness messages at low vehicle densities periodically, and used the Manhattan grid model to simulate the street environment as well as gave the obstacle model. In [10], Reis et al found parked cars could indeed serve both as RSUs and an extension to vehicular infrastructure deployments. Besides, the work investigated how to select a suitable parked car to be an RSU, and proposed an on-line algorithm to maximize the coverage by activating the least parked cars.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Eckhoff et al [5] introduced a novel scheme to emit cooperative awareness messages at low vehicle densities periodically, and used the Manhattan grid model to simulate the street environment as well as gave the obstacle model. In [10], Reis et al found parked cars could indeed serve both as RSUs and an extension to vehicular infrastructure deployments. Besides, the work investigated how to select a suitable parked car to be an RSU, and proposed an on-line algorithm to maximize the coverage by activating the least parked cars.…”
Section: Related Workmentioning
confidence: 99%
“…Then w sri = N0 2Ps , w rid = N0 2Pri . Because the K 1 (x) function converges to 1/x when x approaches zero, the formula (10) can be simplified to…”
Section: A Outage Probability Of the Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, parked vehicles may act as RSUs and they can facilitate data traffic routing (e.g. safety messages broadcast) along with the existing dedicates RSUs in urban vehicular networks [36]. By doing so, additional expenses for deploying dedicates RSUs can be avoided successfully.…”
Section: Introductionmentioning
confidence: 99%
“…Vehicles that park in urban areas can be leveraged to take on the roles of fixed roadside units, positioning themselves as an effective alternative to costly deployments of network infrastructure. Research shows that parked cars equipped with 802.11p technology are able to self-organize and create a vehicular support network in an urban area, replacing or augmenting existing roadside units [9], [10]. Such a vehicular support network, created from parked cars, is able to serve an important role in achieving the vision of a Smarter City: the ubiquity of parked cars in the urban area allows them to form widespread mesh networks, while their On-Board Unit (OBU) hardware lets them be aware of nearby vehicle activity and monitor the city's transportation resources.…”
Section: Introductionmentioning
confidence: 99%